Retinoids and breast cancer: new clues to increase their activity and selectivity - Garattini, Enrico (BioMed Central, 2012)
All-trans retinoic acid and derivatives (retinoids) are promising agents in the management of certain hematologic malignancies and solid tumors, including breast cancer. Retinoids are endowed with anti-proliferative, cyto-differentiating and apoptotic effects that are largely mediated by activation of the nuclear hormone retinoic acid receptors RARα, RARβ and RARγ. These are ligand-dependent transcriptional factors controlling the expression of numerous genes. The relative importance of each receptor subtype for the anti-tumor activity of retinoids is largely unknown. Clarification of this point is of fundamental importance for the rational design of retinoid-based therapeutic approaches aimed at controlling a heterogeneous type of tumors, like breast cancer.